Impact of chronic potassium binder treatment on the clinical outcomes in patients with hyperkalemia: Results of a nationwide hospital-based cohort study - Kanda, Eiichiro; Morita, Naru; Yajima, Toshitaka (Frontiers in Physiology, 2023)
Introduction: Hyperkalemia (HK) is a common disorder in patients with heart failure or chronic kidney disease, and potassium binders (PBs) are recommended to control serum potassium (S-K) levels. Although HK is often a chronic condition, short-term and intermittent PBs treatment has been largely applied to control S-K levels, and little is known about the impact of long-term and chronic PBs treatment on clinical outcomes. Method: This retrospective cohort study was conducted using a Japanese claims database (April 2008–September 2018). HK was defined as at least two S-K ≥5.1 mmol/L within a 12-month(M) interval. The index date was defined as the initial PB prescription date, and the S-K values were examined at 3M, 6M, and 12M after the index. The medication possession ratio (MPR) was used to evaluate the length of the prescribed period of PB, as prescription refill was not allowed in Japan. Clinical outcomes were analyzed by comparing MPR <80% to MPR ≥80% using Cox proportional hazards regression. Results: We found 4,321 patients with HK and were on initial PB treatments, and 993 and 3,328 patients were categorized in the MPR <80% and MPR ≥80% groups, respectively. The mean prescription days ±SD in the MPR <80% and MPR ≥80% groups were 114.7 ± 9.1 and 1151.2 ± 22.5, respectively. S-K value with adjustment by covariates in MPR <80% and MPR ≥80% groups were 5.62 (95% CI: 5.57–5.68) and 5.72 (95% CI: 5.68–5.76) at index followed by 4.65 (95% CI: 4.58–4.71) and 4.57 (95% CI: 4.51–4.62) at 3M, respectively. The hazard ratios of incidence rates in hospitalization was 1.41 (p < 0.001), introduction of renal replacement therapy was 1.25 (p < 0.003), recurrent HK was 1.67 (p < 0.001), and decreased eGFR was 1.41 (p < 0.001), respectively. Conclusion: These results indicate a higher risk of adverse outcomes when PBs were not prescribed chronically, whereas S-K levels were similarly controlled. Chronic control with continued PBs rather than temporary treatment may be associated with the reduction of adverse clinical outcomes in patients with HK.